Assessment of Early Pain Management in Fracture Cases in the Emergency Department: Evidence from Clinical Practice - Waode Ryanti Yakut; Haeril Amir; Rahmat Hidayat (PT.Mantaya Idea Batara, 2025)
Open fractures are serious injuries in which bone fragments are directly exposed to the external environment, resulting in a significantly higher risk of infection compared to closed fractures. Patients presenting with fractures to the emergency department (ED) are initially assessed using the airway, breathing, circulation, disability, and exposure (ABCDE) approach. This serves as one of the strategies to reduce the pain experienced by patients with fractures. This study employed a descriptive approach with a descriptive case study method, aiming to provide an overview of the initial management of a patient with an open fracture of the right tibia. General initial management of pain included immobilization techniques, hemorrhage control, and the administration of analgesics, which were found to reduce pain levels and prevent further complications. The study concludes that general initial management is an essential and effective approach in the early treatment of open fracture patients. This process not only focuses on medical aspects but also addresses the holistic nursing needs of patients. Further research is recommended to evaluate the long-term effectiveness of general initial management.